Digital Logic Design Chapter 3 Digital Systems and

  • Slides: 31
Download presentation
Digital Logic Design Chapter 3 Digital Systems and Binary Numbers Al-Mustansiriyah University College of

Digital Logic Design Chapter 3 Digital Systems and Binary Numbers Al-Mustansiriyah University College of Science Computer Department Dr. Ghassan M. Al-Saddi

Outline of Chapter 3 © 3. 1 Simplification of Boolean Functions © 3. 2

Outline of Chapter 3 © 3. 1 Simplification of Boolean Functions © 3. 2 Product of Sum simplification © 3. 3 Don’t- Care Condition

Another method of simplification of Boolean function is Karnaugh – Map (K-Map). This map

Another method of simplification of Boolean function is Karnaugh – Map (K-Map). This map is a diagram made of squares, each square represent one minterms, and there are several types of K-|Map depending on the number of variables in Boolean function.

Two-Variable Map A two-variable map u Four minterms u x' = row 0 u

Two-Variable Map A two-variable map u Four minterms u x' = row 0 u x = row 1 u y' = column 0 u y = column 1 u A truth table in square diagram u Fig. (a) xy = m 3 u Fig. (b) x+y = x'y+xy' +xy = m 1+ m 2+m 3

A Three-variable Map u Eight minterms u Any two adjacent squares in the map

A Three-variable Map u Eight minterms u Any two adjacent squares in the map differ by only on variable q q q e. g. , m 5 and m 7 can be simplified m 5+ m 7 = xy'z + xyz = xz (y'+y) = xz m 0 and m 2 (m 4 and m 6) are adjacent m 0+ m 2 = x'y'z' + x'yz' = x'z' (y'+y) = x'z' m 4+ m 6 = xy'z' + xyz' = xz' (y'+y) = xz'

Ex Simplify the Boolean function F(x, y, z) = S(2, 3, 4, 5) F(x,

Ex Simplify the Boolean function F(x, y, z) = S(2, 3, 4, 5) F(x, y, z) = Σ(2, 3, 4, 5) = x'y + xy'

Ex Simplify F(x, y, z) = S (3, 4, 6, 7) F(x, y, z)

Ex Simplify F(x, y, z) = S (3, 4, 6, 7) F(x, y, z) = S(3, 4, 6, 7) = yz+ xz'

Four adjacent Squares Consider four adjacent squares um 0+m 2+m 4+m 6= x'y'z'+x'yz'+xy'z'+xyz' =x'z'(y'+y)

Four adjacent Squares Consider four adjacent squares um 0+m 2+m 4+m 6= x'y'z'+x'yz'+xy'z'+xyz' =x'z'(y'+y) +xz'(y'+y)= x'z' + xz‘= z' um 1+m 3+m 5+m 7 = x'y'z+x'yz+xy'z+xyz =x'z(y'+y) + xz(y'+y) =x'z + xz = z

Ex Simplify F(x, y, z) = S(0, 2, 4, 5, 6) = z'+ xy'

Ex Simplify F(x, y, z) = S(0, 2, 4, 5, 6) = z'+ xy'

Ex let F = A'C + A'B + AB'C + BC a) Express it

Ex let F = A'C + A'B + AB'C + BC a) Express it in sum of minterms. b) Find the minimal sum of products expression F(A, B, C) = S(1, 2, 3, 5, 7) = C + A'B A'C + A'B + AB'C + BC = C + A'B

Four-Variable Map © The map u u 16 minterms Combinations of 2, 4, 8,

Four-Variable Map © The map u u 16 minterms Combinations of 2, 4, 8, and 16 adjacent squares

Adjacent Squares

Adjacent Squares

n Ex Simplify F(w, x, y, z) = S(0, 1, 2, 4, 5, 6,

n Ex Simplify F(w, x, y, z) = S(0, 1, 2, 4, 5, 6, 8, 9, 12, 13, 14) F(w, x, y, z) = Σ(0, 1, 2, 4, 5, 6, 8, 9, 12, 13, 14) = y' + w' z' +xz'

n Ex Simplify F = A B C + B CD + A B

n Ex Simplify F = A B C + B CD + A B C D + AB C = B D + B C +A CD

Five-Variable Map © Map for more than four variables becomes complicated u Five-variable map:

Five-Variable Map © Map for more than four variables becomes complicated u Five-variable map: two four-variable map (one on the top of the other).

© Or the map is like this

© Or the map is like this

Ex Simplify F = S(0, 2, 4, 6, 9, 13, 21, 23, 25, 29,

Ex Simplify F = S(0, 2, 4, 6, 9, 13, 21, 23, 25, 29, 31) F = A'B'E'+BD'E+ACE

Ex Simply the following Boolean functions using K –Map? 1 - F = X

Ex Simply the following Boolean functions using K –Map? 1 - F = X Y Z + X Y Z F = X Y + X Y 2 - F = X Y Z + X Y Z F = Y Z + X Z 3 - F = A C + A B C + B C F = C + A B 4 - F ( X, Y, Z ) = Σ ( 0, 2, 4 , 5 , 6 ) F ( X, Y, Z ) = Z + X Y 5 - F ( X, Y, Z, W ) = Σ ( 0, 1, 2, 4, 5, 6, 8 , 9 , 12, 13, 14 ) F ( X, Y, Z, W ) = Z + X W + Y W 6 - F = A B C + B C D + A B C F ( A, B, C, D ) = B D + B C + A C D

H. W Simplify the following functions in sum of product using Kmap 1 -

H. W Simplify the following functions in sum of product using Kmap 1 - F = X Y + X Y W + W ( X Y + X Y ) 2 - F = A B D + A C D + A B D 3 - F ( A, B , C, D ) = Π ( 2, 3, 6, 7, 8, 9, 10 , 11, 12, 13, 14 )

Product of Sum simplification In previous examples the simplification in Sum of Product form

Product of Sum simplification In previous examples the simplification in Sum of Product form and each minterms represented by 1 (one) in K-map and each missing term in the function is a complement of the function and represented by 0 (zero) in k-map and the simplified expression obtained F (the complement of the function).

Sum-of-Minterm Procedure n Consider the function defined in Table; q In sum-of-minterm: q In

Sum-of-Minterm Procedure n Consider the function defined in Table; q In sum-of-minterm: q In sum-of-maxterm: q Taking the complement of F

Ex Simplify F = S (0, 1, 2, 5, 8, 9, 10) into 1

Ex Simplify F = S (0, 1, 2, 5, 8, 9, 10) into 1 - sum-of-products form. 2 - product-of-sums form Sol : 1 – Sum of Products (minterms) a) F(A, B, C, D)= S(0, 1, 2, 5, 8, 9, 10) = B'D'+B'C'+A'C'D b) F' = AB+CD+BD' Apply De. Morgan's theorem; F=(A'+B')(C'+D')(B'+D)

n Gate implementation of the function of Example Sum-of products form Product-of sums form

n Gate implementation of the function of Example Sum-of products form Product-of sums form

Ex Obtained the simplified expression in Product of Sums F = ( A' +

Ex Obtained the simplified expression in Product of Sums F = ( A' + B' + D ) ( A' + D' ) ( A + B' + C + D ) F' = A B D' + A D + A' B' D + A' B C' D' CD AB 00 01 11 10 00 01 0 0 11 0 0 10 0 F' = A B + B' D + B C' D' F = ( A' + B' ) ( B + D' ) ( B' + C + D )

Ex Obtained the simplified expression in Product of Sums F ( A, B, C,

Ex Obtained the simplified expression in Product of Sums F ( A, B, C, D ) = Π ( 0, 1, 2, 3, 4, 10, 11) CD AB 00 00 01 0 10 01 11 0 0 10 0 F' = A' B' + A' C' D' + B' C F = ( A + B ) ( A + C + D ) ( B + C' )

H. W : Obtained the simplified expression of the following functions in 1 -

H. W : Obtained the simplified expression of the following functions in 1 - Sum of Products 2 - Product of Sums 1 - F = X' Y' + Y' Z' + Y Z' + X Y Z 2 - F ( X, Y, Z, W) = Π ( 1, 3 , 5, 7, 13, 15 ) 3 - F = ( A + B' + D ) ( A' + B + D) ( C + D ) ( C' + D' )

Don't-Care Conditions © The “Don’t Care” conditions allow to replace the empty cell of

Don't-Care Conditions © The “Don’t Care” conditions allow to replace the empty cell of a K-Map to form a grouping of the variables. © While forming groups of cells, we can consider a “Don’t Care” cell as either 1 or 0 or we can simply ignore that cell. © Therefore, “Don’t Care” condition can help to form a larger group of cells. © A Don’t Care cell can be represented by a cross(X) in K-Maps representing a invalid combination. © These values used in simplification with F and F'.

Ex Simplify the Boolean function F in 1 - Sum of Products (S. O.

Ex Simplify the Boolean function F in 1 - Sum of Products (S. O. P) 2 - Product of Sums (P. O. S) F( X, Y, Z, W)=Σ(1, 3, 7, 11, 15 ) d(X, Y, Z, W )=Σ (0, 2 , 5 ) Sol 1 - Sum of Products CD AB 00 00 X 01 11 10 1 1 X X 1 1 1 F ( X, Y, Z, W) = Z W + X' Y' 2 – Product of Sums CD AB 00 00 X 01 0 10 0 01 11 10 X X 0 0 0 F ( X, Y, Z, W) = W' + X Z' F ( X, Y, Z, W) = W ( X' + Z )

Ex Simplify the Boolean function F in 1 - Sum of Products 2 -

Ex Simplify the Boolean function F in 1 - Sum of Products 2 - Product of Sums using don’t care condition F = A C E + A' C D' E' + A' C' D E D = D E' + A' D' E + A D' E' Sol F = A C E. 1 + A C D E = A C D E + A C D' E + A' C D' E' + A' C' D E D = D E' ( A + A' ) + A' D' E ( C + C' ) + A D' E' ( C + C' ) = A D E' ( C + C' ) + A' C D' E + A' C' D' E + A C D' E' + A C' D' E' = A C D E' + A C' D E' + A' C D' E + A' C' D' E +A C D' E' + A C' D' E'

1 - Sum of Products DE AC 00 00 01 1 11 X 10

1 - Sum of Products DE AC 00 00 01 1 11 X 10 X 01 11 10 X 1 X 1 X X S. O. P F ( A, C, D, E ) = A C + C E' + A' C' D 2 – Product of Sums DE AC 00 00 0 01 11 X 10 X 01 11 X X 10 X X 0 0 X P. O. S. F'( A, C, D, E )= A C' + C' D' + A' C D F ( A, C, D, E ) = (A' + C ) (C + D ) ( A + C ' + D' )

H. W. Simplify the Boolean function F in Sum of Products using don’t care

H. W. Simplify the Boolean function F in Sum of Products using don’t care condition F = B' C' D' + B C D' + A B C' D D = B' C D' + A' B C' D'